2004
DOI: 10.1038/sj.mp.4001511
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in schizophrenia: evidence for compromised brain metabolism and oxidative stress

Abstract: The etiology and pathophysiology of schizophrenia remain unknown. A parallel transcriptomics, proteomics and metabolomics approach was employed on human brain tissue to explore the molecular disease signatures. Almost half the altered proteins identified by proteomics were associated with mitochondrial function and oxidative stress responses. This was mirrored by transcriptional and metabolite perturbations. Cluster analysis of transcriptional alterations showed that genes related to energy metabolism and oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
505
2
8

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 727 publications
(561 citation statements)
references
References 67 publications
46
505
2
8
Order By: Relevance
“…Several postmortem studies in schizophrenia have demonstrated reduced expression of oligodendrocyte-related genes, [17][18][19][20][21][67][68][69][70][71][72] some of which may be susceptibility genes for schizophrenia. 33,[72][73][74][75] Moreover, several studies have evidence for deficits in oligodendrocytes in the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Several postmortem studies in schizophrenia have demonstrated reduced expression of oligodendrocyte-related genes, [17][18][19][20][21][67][68][69][70][71][72] some of which may be susceptibility genes for schizophrenia. 33,[72][73][74][75] Moreover, several studies have evidence for deficits in oligodendrocytes in the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the schizophrenia analysis have been previously published, and none of the findings in bipolar disorder described here were found in the schizophrenia samples. 16 Both gray and white matter bipolar tissue were separated well from the corresponding control tissue based on PLS-DA models (Figures 1b and c). A number of metabolites were found to contribute to this separation including myo-inositol, glutamate, lactate, phosphocholine and creatine ( Figure 1a; Table 2).…”
Section: Post-mortem Brain Tissue Analysismentioning
confidence: 92%
“…Although there are many platforms for metabolic profiling (for example, LC-MS, GC-MS, NMR, electrocapillary phoresis-MS), no one technology gives complete coverage of the metabonome. This technique has been used extensively in studies on schizophrenia, [16][17][18][19] Alzheimer's disease, 20 Huntington's disease, 21 Batten disease 22 and human brain tumors 23 (for detailed reviews on metabonomics, see Holmes et al 24 and Lenz and Wilson 25 ). These studies have identified a number of biochemical alterations that may be occurring as part of the pathogenesis of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These are fructose bisphosphate aldolase C (FBA-C, absent in schizophrenia), citrate synthase (absent in schizophrenia), two spots corresponding to isocitrate dehydrogenase (À1.692 and absent), and NADH ubiquinine oxidoreductase (À1.944). FBA-C, a glycolytic enzyme, has previously been implicated in schizophrenia with increased levels in the frontal cortex proteome of schizophrenia patients, 19 reduced levels in both the gray and white matter of the PFC proteome 18 and an increased immunoreactivity in schizophrenia CSF. 33 Citrate synthase and isocitrate dehydrogenase form a part of the citric acid cycle.…”
Section: Metabolismmentioning
confidence: 99%
“…Proteomics, with the ability to investigate the translation of genomic information together with co-and post-translational modifications, 17 offers an approach to studying the global changes in protein expression and modification caused by neuropathologies such as Alzheimer's Disease (AD), Down Syndrome (DS) and schizophrenia. Previous findings of proteomic investigations into schizophrenia include various proteins associated with metabolism and oxidative stress to be differentially expressed in the prefrontal cortex (PFC) in the disease state relative to controls, 18 proteins previously implicated in schizophrenia as well as some novel proteins to be altered in the frontal cortex, 19 and four of 18 altered proteins in the schizophrenia hippocampus mapping to chromosome 6q. 20 In addition, a proteomic study investigating the cerebrospinal fluid (CSF) in schizophrenia identified 54 different gene products, 17 leading to new and refined hypotheses into the molecular mechanisms underlying this disease.…”
Section: Introductionmentioning
confidence: 99%